1994
DOI: 10.1007/s001250050176
|View full text |Cite
|
Sign up to set email alerts
|

Are gender differences in cardiovascular disease risk factors explained by the level of visceral adipose tissue?

Abstract: Summary It has been suggested that the lower prevalence of cardiovascular disease in women before menopause in comparison with men may be explained by differences in body fat distribution, plasma lipoprotein levels and indices of plasma glucose-insulin homeostasis. Thus, gender differences in visceral adipose tissue accumulation measured by computed tomography and metabolic variables were studied in 80 men and 69 pre-menopausal women, aged 23-50 years. Despite the fact that women had higher levels of total bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
4
40
2
4
Order By: Relevance
“…Caucasian men in the present study showed a positive association between TAG concentrations and waist (r ¼ 0.275, P ¼ 0.04), BMI (r ¼ 0.381, P ¼ 0.01) and suprailiac (r ¼ 0.314, P ¼ 0.04). These data support findings from other studies performed on Caucasian men, 21,22,[56][57][58][59] although not all. 30,31 However, the expected positive association between waist (or any other measure of adiposity) and circulating TAG was not observed in the Sikh men.…”
Section: Discussionsupporting
confidence: 91%
“…Caucasian men in the present study showed a positive association between TAG concentrations and waist (r ¼ 0.275, P ¼ 0.04), BMI (r ¼ 0.381, P ¼ 0.01) and suprailiac (r ¼ 0.314, P ¼ 0.04). These data support findings from other studies performed on Caucasian men, 21,22,[56][57][58][59] although not all. 30,31 However, the expected positive association between waist (or any other measure of adiposity) and circulating TAG was not observed in the Sikh men.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies had reported sex differences in fasting plasma lipoprotein-lipid concentrations, including lower TG and higher HDL cholesterol levels in women than in men. 33,34 In the present study, compared with white women, white men were characterized by higher plasma TG and apoB concentrations as well as by lower HDL cholesterol levels. These differences were also noted in blacks.…”
Section: Effect Of Sexmentioning
confidence: 41%
“…Although increase in gynoid adipose tissue also correlates to CVD risk in obese women (mainly due to the general increase in weight), high storage of fat in the gynoid region relative to total fat is negatively related to CVD risk (Wiklund et al, 2008). Excessive accumulation of fat in the abdominal region has strongly been associated with metabolic alterations such as disturbed plasma lipoprotein profiles, hyperinsulinaemia, insulin resistance, and glucose intolerance (Lemieux et al, 1994).…”
Section: Introductionmentioning
confidence: 99%